Nānāsāheba Peśave : hrdgata dākhaviṇāryā mūḷa patr̃āsaha - Sardesai, Govind Sakharam, 1865-1959 (SAMP early 20th-century Indian books project, 1926)
On the life and activities of Balaji Baji Rao, 1721-1761, Indian revolutionary leader against Mogul Empire.